FACTORS AFFECTING ONLINE BUYING BEHAVIOR FOR MILLENIAL - Kerenhapukh Devi MentariUtomo; Jony Oktavian Haryanto (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2021)
The rapid development of information technology including the internet had a great impact on all aspects including the development of business and marketing. This study aims to determine the effect of price perceptions, brand image and website quality on customer satisfaction and the impact to customer loyalty in Shopee’s online shopping which revolves around millennial communities in Jabodetabek area. The purpose of this research is to see the effect of price perception, brand image, and website quality that has been given by Shopee in influencing customer satisfaction and loyalty. Respondents in this study were consumers who had purchased products at Shopee, and the researcher used the Structural Equation Model (SEM) method in processing the data obtained from the 200 respondents. From the results of the hypothesis, it shows that price perception, website quality, and brand image don’t have positive effect on customer satisfaction. Other results also suggest that customer satisfaction do have positive effect on customer loyalty.